Bio-oils from microwave pyrolysis of agricultural wastes - Sharifah Mona, Abdul Aziz; Rafeah, Wahi; Zainab, Ngaini; Sinin, Hamdan (Elsevier, 2013)
Pyrolysis of palm kernel shell (PK), wood chips (WC) and sago wastes (SW) was performed onmicrowave irradiation at different heating time, at moderate temperature 250–390 °C. Samples were placed in quartz reactor and subjected tomicrowave heating in inert atmosphere to afford bio-oils (PKO,WCO and SWO). The highest calorific values recorded are 27.19 MJ/kg, 25.99 MJ/kg, and 21.99 MJ/kg for PKO, WCO and SWO. FTIR spectroscopy showed the presence of functional groups such as phenol, alcohols, ketones, aldehydes and carboxylic acids. The GCMS showed that PKO, WCO and SWO consist of significant quantities of potentially high value hydrocarbons such as monoaromatic hydrocarbons and phenolic compounds. Importantly, the bio-oils do not contain carcinogenic polyaromatic hydrocarbons (PAH). Upon further refining, the bio-oils have a potential as valuable source for fuel or chemical feedstocks.